2011
DOI: 10.1016/j.gene.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genes encoding trypsin-like enzymes from Aedes aegypti larvae and identification of digestive enzymes

Abstract: Trypsin-like enzymes play an important role in the Aedes aegypti digestive process. The trypsin-like enzymes present in adults were characterized previously, but little is known about trypsins in larvae. In the present work, we identified one of the trypsin enzymes from Ae. aegypti larval midgut using a library of trypsin gene fragments, which was the sequence known as AAEL005607 from the Ae. aegypti genome. Quantitative PCR analysis showed that AAEL005607 was transcribed in all larval instars, but it was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…This result was corroborated by the quantitative in-solution assays using the fluorogenic substrate Z-Phe-Arg-AMC. Quantitative differential expression in larval instars has also been observed by other authors, specifically in the intestine, using alternative methods [21,39,56]. In the present study, the proteolytic classes of the enzymes were characterized using different inhibitors, revealing that peptidases from the four larval instars were inhibited by PMSF, an inhibitor of trypsin and chymotrypsin, and TLCK, an inhibitor of trypsin.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This result was corroborated by the quantitative in-solution assays using the fluorogenic substrate Z-Phe-Arg-AMC. Quantitative differential expression in larval instars has also been observed by other authors, specifically in the intestine, using alternative methods [21,39,56]. In the present study, the proteolytic classes of the enzymes were characterized using different inhibitors, revealing that peptidases from the four larval instars were inhibited by PMSF, an inhibitor of trypsin and chymotrypsin, and TLCK, an inhibitor of trypsin.…”
Section: Discussionsupporting
confidence: 76%
“…These results are in agreement with a recent transcriptome study showing that 12 serine peptidases-like genes were preferential expressed in the larvae of Ae. aegypti [39,59]. The broad spectrum of enzymatic activities detected in the larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes have been reported to be involved in protein digestion for nutrition and development throughout the Ae. aegypti life cycle . After LsCTI had been demonstrated in vitro to inhibit the midgut enzymes of the larvae of this mosquito, in vivo assays were performed to determine how this inhibitor affects mosquito development.…”
Section: Resultsmentioning
confidence: 99%
“…The genomes of Anopheles gambiae , Drosophila melanogaster and Bombyx mori contain 305, 206 and 143 SP or SPH genes, respectively (Zdobnov et al ., ; Ross et al ., ; Zhao et al ., ). Many studies have shown that insect SPs play important roles in dietary protein digestion (Terra & Ferreira, ; Lehane et al ., ; Herrero et al ., ; Soares et al ., ), molting (Samuels et al ., ; Wei et al ., ; Liu et al ., ; He et al ., ), metamorphosis (Tsuji et al ., ; Danielli et al ., ; Kaji et al ., ) and the immune response (Jiang et al ., ; Gorman et al ., ; An et al ., ). Based on the residue composition of the substrate‐specific pocket, SPs are mainly categorized as trypsin (residues D189, G216 and G226), chymotrypsin (residues S189, G216 and G226) or elastase (residues V216 and T226) (Perona & Craik, , Hedstrom, ).…”
Section: Introductionmentioning
confidence: 99%